C.3 - "Jakhar, Bal Ram" (New Delhi, 1982)
The book presents the dynamic Lok Sabha Speaker Dr. Bal Ram Jakhar's musings, reactions and thoughts on some facets of parliamentary institutions, processes and procedures as also other matters of parliamentary and public interest.
Keywords: Parliamentary practice